EXPLORING CONSTRUCTED VISUAL REPRESENTATIONS OF SELF: A SEMIOTIC ANALYSIS OF INSTAGRAM AND FACEBOOK SELFIES - Tandi, Yuzril Reynaldi; Mahmud, Murni (Faculty of Languages and Literature, Universitas Negeri Makassar, 2025)
This research is a study on